Educational Inequality and Public Policy Preferences: Evidence from Representative Survey Experiments - Philipp Lergetporer; Katharina Werner; Ludger Woessmann (Institute of Labor Economics (IZA), 2018)
To study how information about educational inequality affects public concerns and policy preferences, we devise survey experiments in representative samples of the German population. Providing information about the extent of educational inequality strongly increases concerns about educational inequality but only slightly affects support for equity-oriented education policies, which is generally high. The small treatment effects are not due to respondents' failure to connect policies with educational inequality or aversion against government interventions. Support for compulsory preschool is the one policy with a strong positive information treatment effect, which is increased further by informing about policy effectiveness.
Keywords: D30; H52; I24; H11; D63; D83; D72; P16; 330; inequality; education; information; survey experiment